Migration in Vietnam : New Evidence from Recent Surveys - Coxhead, Ian (World Bank, Hanoi, 2016)
The authors investigate determinants of individual migration decisions in Vietnam, a country with increasingly high levels of geographical labor mobility. Using data from the Vietnam Household Living Standards Survey (VHLSS) of 2012, the authors find that probability of migration is strongly associated with individual, household and community-level characteristics. The probability of migration is higher for young people and those with post-secondary education. Migrants are more likely to be from households with better-educated household heads, female-headed households, and households with higher youth dependency ratios. Members of ethnic minority groups are much less likely to migrate, other things equal. Using multinomial logit methods, we distinguish migration by broad destination, and find that those moving to Ho Chi Minh City or Hanoi have broadly similar characteristics and drivers of migration to those moving to other destinations. The authors also use VHLSS 2012 together with VHLSS 2010, which allows us to focus on a narrow cohort of recent migrants, those present in the household in 2010, but who have moved away by 2012. This yields much tighter results. For education below upper secondary school, the evidence on positive selection by education is much stronger. However, the ethnic minority ‘penalty’ on spatial labor mobility remains strong and significant, even after controlling for specific characteristics of households and communes. This lack of mobility is a leading candidate to explain the distinctive persistence of poverty among Vietnam’s ethnic minority populations, even as national poverty has sharply diminished.